Markers of Response to Antiangiogenic Therapies in Colorectal Cancer: Where are We Now and What should be Next?. (January 2016) - Cidon, E. Una; Alonso, P.; Masters, B.
Despite advances in the treatment of colorectal cancer (CRC), it remains the second most common cause of cancer-related death in the Western world. Angiogenesis is a complex process that involves the formation of new blood vessels from preexisting vessels. It is essential for promoting cancer survival, growth, and dissemination. The inhibition of angiogenesis has been shown to prevent tumor progression experimentally, and several chemotherapeutic targets of tumor angiogenesis have been identified. These include anti-vascular endothelial growth factor (VEGF) treatments, such as bevacizumab (a VEGF-specific binding antibody) and anti-VEGF receptor tyrosine kinase inhibitors, although antiangiogenic therapy has been shown to be effective in the treatment of several cancers, including CRC. However, it is also associated with its own side effects and financial costs. Therefore, the identification of biomarkers that are able to identify patients who are more likely to benefit from antiangiogenic treatment is very important. This article intends to be a concise summary of the potential biomarkers that can predict or prognosticate the benefit of antiangiogenic treatments in CRC, and also what we can expect in the near future.